2014
DOI: 10.1002/eji.201344388
|View full text |Cite
|
Sign up to set email alerts
|

Midline 1 directs lytic granule exocytosis and cytotoxicity of mouse killer T cells

Abstract: Midline 1 (MID1) is a microtubule-associated ubiquitin ligase that regulates protein phosphatase 2A activity. Loss-of-function mutations in MID1 lead to the X-linked Opitz G/BBB syndrome characterized by defective midline development during embryogenesis. Here, we show that MID1 is strongly upregulated in murine cytotoxic lymphocytes (CTLs), and that it controls TCR signaling, centrosome trafficking, and exocytosis of lytic granules. In accordance, we find that the killing capacity of MID1 −/− CTLs is impaired… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 49 publications
5
30
0
Order By: Relevance
“…In contrast, the primary response in the draining LN was not affected in MID1 -/- mice. At first sight this may seem to be a paradox; however, we have recently shown that MID1 is weakly expressed in thymocytes and naïve T cells, and that it does not affect activation of naïve CD8 + T cells in vitro 28. Thus, our data supported that the impaired polarization and migration of MID1 -/- CTLs translated into altered CTL responses in vivo and confirmed that MID1 does not affect activation of naïve CD8 + T cells.…”
Section: Discussionsupporting
confidence: 73%
See 4 more Smart Citations
“…In contrast, the primary response in the draining LN was not affected in MID1 -/- mice. At first sight this may seem to be a paradox; however, we have recently shown that MID1 is weakly expressed in thymocytes and naïve T cells, and that it does not affect activation of naïve CD8 + T cells in vitro 28. Thus, our data supported that the impaired polarization and migration of MID1 -/- CTLs translated into altered CTL responses in vivo and confirmed that MID1 does not affect activation of naïve CD8 + T cells.…”
Section: Discussionsupporting
confidence: 73%
“…Whether MID1 plays any role after embryogenesis was unknown until recently, where it was found that MID1 is involved in induction of allergic airway inflammation in the bronchial epithelium [42]. Furthermore, we recently found that MID1 is up-regulated in CTLs where it directs lytic granule exocytosis and cytotoxicity [28]. In the present study we found that MID1 predominantly localizes to the uropod and that a minor part radiates out from the uropod towards the leading edge in migrating CTLs.…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations